Implementasi Analisis Proses Bisnis Sebagai Upaya Pengurangan Biaya - Aniek Wijayanti (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2019)
Business Process Analysis can be used to eliminate or reduce a waste cost caused by non value added activities that exist in a process. This research aims at evaluating activities carried out in the natural material procurement process in the PT XYZ, calculating the effectiveness of the process cycle, finding a way to improve the process management, and calculating the cost reduction that can achieved by activity management. A case study was the approach of this research. The researcher obtained research data throughout deep interviews with the staff who directly involved in the process, observation, and documentation of natural material procurement. The result of this study show that the effectiveness of the process cycle of natural material procurement in the factory reached as much as 87,1% for the sand material and 72% for the crushed stone. This indicates that the process still carry activities with no added value and still contain ineffective costs. Through the Business Process Mechanism, these non value added activities can be managed so that the process cycle becomes more efficient and cost effectiveness is achieved. The result of the effective cycle calculation after the management activities implementation is 100%. This means that the cost of natural material procurement process has become effective. The result of calculation of the estimated cost reduction as a result of management activity is as much as Rp249.026.635,90 per year.